Getting Our Fingers on the Pulse of Slow-Growing Bacteria in Hard-To-Reach Places - Gallagher, Tara (J Bacteriol, 2018)
Chronic infections with slow-growing pathogens have plagued humans throughout history. However, assessing the identities and growth rates of bacteria in an infection has remained an elusive goal. Neubauer et al. (J. Bacteriol. 200:e00365-18, 2018, https://doi.org/10.1128/JB.00365-18) combine two cutting-edge approaches to make progress on both fronts: probing specific RNA molecules to assess the identity of actively transcribing microbes and measuring growth rates through incorporation of stable isotope labels. They found that growth rates of pathogens were relatively stable during antibacterial therapy. The article delves into a basic and unanswered question that gets to the heart of understanding infection: what are the microbial growth rates?